BIMBINGAN DAN KONSELING UNTUK MOTIVASI BELAJAR - Dian Eka Priyantoro (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
In the learning process, motivation is necessary both performed inside and outside the classroom, because someone who does not have the motivation to learn, he will be difficult for doing in learning activities. Someone who performs learning activities without any motivation from outside himself is an intrinsic motivation. It is very important in learning activities for students. However, someone who does not have a desire to learn, push from outside himself is expected extrinsic motivation. The challenge of professional teacher is how to change the students who do not have motivation to be motivated students in learning through the guidance and counseling in schools.